IDENTIFICATION AND MANAGEMENT OF PARAFFIN IN THE FM-20 WELL FROM THE WELL HEAD TO THE MANIFOLD OF DISTRICT I KAWENGAN - KRISTOFOL WAAS; MICHELLE IVONIE LETLORA (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2022)
Indonesia is one of the oil and gas producing countries in the world. This natural wealth needs to be utilized as much as possible. The main objective to be achieved in the production operation of an oil and gas well, is to increase the rate of production until it reaches its peak. The sharp decline in production volumes and levels of oil production from oil wells is a production problem. Paraffin is a raw material contained in crude oil and is a production problem. The paraffin deposition process can occur in perforations, tubing, flowlines, or surface facilities resulting in decreased production rates. In some cases, paraffin deposits may form at the bottom of the well and in the pore space in a radial direction several inches from the well wall, occurring as a result of the oil cooling below the cloud point. Cloud point and pour point are two things that become certain factors in the characteristics of paraffin. The cloud point is the temperature where the paraffin first begins to precipitate from the crude oil mixture. When the temperature drops, the particles that form the paraffin precipitate attract and bind other paraffin particles into one group. At this point the crude oil will start to look hazy and then can't flow. The condition where crude oil cannot flow is called the pour point. The results obtained by using the method. It can be seen that the Electric Heat Trace in the downstream area (variation 2) will be more effective because paraffin will no longer form in the flowline.